Prospects and Challenges of Proton Conducting Cerates in Electrochemical Hydrogen Devices for Clean Energy Systems: A Review - M. Khalid Hossain; Ranjit C. Das; M. Imran Hossain; M. Atikur Rahman; Prabhu Paramasivam; Ripel Chakma; Mongi Amami; Mohamed H. H. Mahmoud; R. Bousbih; Rajesh Haldhar; Kenichi Hashizume (Global Challenges)
Abstract The growing demand for green energy and global concern about environmental issues raise the demand for alternative, environmentally friendly energy sources. Electrochemical hydrogen devices are widely investigated as a potential solution for clean and renewable energy. Proton‐conducting oxides (PCOs) used as an electrolyte are required in electrochemical devices to transport protons. Chemical stability and proton conductivity are essential properties to evaluate a suitable electrolyte for these devices. Doped cerate‐based materials exhibit excellent proton conductivity and chemical stability, making them suitable as electrolyte materials for hydrogen devices. Techniques including doping, co‐doping, sintering aid, and different fabrication processes enhance the proton conductivity and mechanical stability of proton‐conducting materials. This paper highlights the current development of cerate‐based PCOs used as an electrolyte in electrochemical devices named hydrogen pumps, hydrogen isotope separation systems, tritium recovery systems, and hydrogen sensors, which could be used in the nuclear fusion reactors, among other electrochemical hydrogen devices. The center part of this review paper summarizes the most recent research studies on these applications and offers a thorough understanding of the impact of doping, different synthesis methods, sintering aids, and operating environments on the composition, morphology, and performance of cerate electrolyte materials. The challenges and prospects of proton‐conducting cerates are also discussed. This paper provides an insightful pathway for the researcher to further research in this field.